دور الرقابة الداخلية في تحقيق جودة التقارير المالية دراسة تطبيقية على وزارة المالية السودانية : The Role of Internal Control in Achieving Quality Financial Reports: A Case Study of the Sudanese Ministry of Finance - محمد فضل المولى عبد الوهاب حماد (Journal of North African Economies, 2025)
This research aimed to identify the role of internal control in achieving the quality of financial reports by examining the statistically significant relationship between the level of administrative control and the quality of financial reports in the Sudanese Ministry of Finance, the statistically significant relationship between the level of internal control and the quality of financial reports in the Sudanese Ministry of Finance, and the statistically significant relationship between accounting control and the quality of financial reports in the Sudanese Ministry of Finance. Based on these objectives, hypotheses were formulated. The research employed a descriptive-analytical approach. The researcher distributed 115 questionnaires electronically to the study population, and 100 valid questionnaires were returned for analysis. After the study and analysis, the following results were obtained: the hypothesis was confirmed, indicating that there is a statistically significant relationship between the level of administrative control and the quality of financial reports in the Ministry of Finance. The chi-square analysis revealed a statistically significant relationship between the level of administrative control (independent variable) and the quality of financial reports at the Ministry of Finance (dependent variable). The calculated chi-square value was 197.66, which is greater than the critical chi-square value (4.13–4.95) with 1–2 degrees of freedom and a p-value of 0.00 for all statements. This is statistically significant at the 0.000 level, meaning that increased attention to the level of administrative control leads to higher quality financial reports at the Ministry of Finance. The median and mode were classified as agreeing, thus explaining the impact on the quality of financial reports. Keywords: Internal control, accounting control, administrative control, internal audit, quality of financial reports, Ministry of Financ